Predictors of poor outcome despite successful endovascular treatment for ischemic stroke: results from the MR CLEAN Registry. (15th July 2021) - van de Graaf, Rob A; Samuels, Noor; Chalos, Vicky; Lycklama a Nijeholt, Geert J; van Beusekom, Heleen; Yoo, Albert J; van Zwam, Wim H; Majoie, Charles B L M; Roos, Yvo B W E M; van Doormaal, Pieter Jan; Ben Hassen, Wagih; van der Lugt, Aad; et al.
Abstract : Background: Approximately one-third of patients with ischemic stroke treated with endovascular treatment do not recover to functional independence despite rapid and successful recanalization. We aimed to quantify the importance of predictors of poor functional outcome despite successful reperfusion. Methods: We analyzed patients from the MR CLEAN Registry between March 2014 and November 2017 with successful reperfusion (extended Thrombolysis In Cerebral Infarction ≥2B). First, predictors were selected based on expert opinion and were clustered according to acquisition over time (ie, baseline patient factors, imaging factors, treatment factors, and postprocedural factors). Second, several models were constructed to predict 90-day functional outcome (modified Rankin Scale (mRS)). The relative importance of individual predictors in the most extensive model was expressed by the proportion of unique added χ 2 to the model of that individual predictor. Results: Of 3180 patients, 1913 (60%) had successful reperfusion. Of these 1913 patients, 1046 (55%) were functionally dependent at 90 days (mRS >2). The most important predictors for mRS were baseline patient factors (ie, pre-stroke mRS, added χ 2 0.16; National Institutes of Health Stroke Scale score at baseline, added χ 2 0.12; age, added χ 2 0.10), and postprocedural factors (ie, symptomatic intracranial hemorrhage (sICH), added χ 2 0.12; pneumonia, added χ 2 0.09). The probability of functional independence for a typical stroke patient with sICH was 54% (95% CI 36% to 72%) lower compared with no sICH, and 21% (95% CI 4% to 38%) for pneumonia compared with no pneumonia. Conclusion: Baseline patient factors and postprocedural adverse events are important predictors of poor functional outcome in successfully reperfused patients with ischemic stroke. This implies that prevention of postprocedural adverse events has the greatest potential to further improve outcomes in these patients.